Morphometric changes in neurons of the suprachiasmatic nucleus of the hypothalamus rats under conditions of light deprivation - Bulyk, R. Ye.; Kryvchanska, M. I.; Burachyk, A. I.; Vlasova, K. V. (Journal of Education, Health and Sport, 2018)
The article deals with the results of studies of the morphometric state of neurons of the suprachiasmatic nuclei (SCN) of the hypothalamus of light-deprived rats. It is established that the duration of the photoperiod has a significant effect on the photoreceptor pacemakers of SCN. In the study of samples taken at 2 pm and 2 am, the light-deprived animals showed a decrease in the morphometric parameters of the pacemaker circadian periodicity in comparison with intact animals and smoothing of diurnal differences in the body area of the neuron of the rat hypothalamus SCN.